Problematika Hukum Renewable Energy Dalam Menciptakan Green Investment Pada Sektor Pariwisata : Peluang Dan Tantangan - Nengah Teguh Artha Sedana; Ni Made Suartini; Lis Julianti; Made Emy Andayani Citra; A.A Kt. Sudiana (Jurnal Hukum Saraswati, 2025)
Indonesia has an important role in improving the global environment. One of the efforts made is to create new economic instruments that aim to reduce risks and provide opportunities for capital flow growth in various sectors. However, to date, it cannot be denied that Indonesia still depends on environmentally unfriendly investments. Monetary policies that rely on extractive investments have become the main choice in Indonesia's financial and development approaches. One way to address challenges in the tourism industry is to make green investments to overcome the negative impacts on environmental damage. The use of energy transition is one solution that can be offered in the development of green investment in the tourism service sector. The research method used in this study is the Socio Legal Research method, where legal materials are collected by systematically compiling and identifying primary, secondary, and tertiary legal materials using the snowball technique. The analysis of legal materials is carried out using descriptive, comparative, evaluative, and argumentative techniques. The results of the study show that the implementation of energy transition policies to realize green investment in Indonesia still faces various obstacles, namely legal inconsistencies related to the use of renewable energy and policies on green investment, as well as economic obstacles related to limited budgets and technology in implementing this energy transition.